Hyperhomocysteinemia and cardiovascular disease: The nutritional perspectives - Pandey, Rajesh (Springer India, 2000)
Several members of the vitamin B-complex family are known to participate in the normal metabolism of homocysteine (Hcy). Leaving aside the genetic determinants of hyperhomocysteinemia (HHC), the deficiencies of these vitamins can also result in HHC. The situation of sustained and long standing HHC is likely to be prevalent in population groups with low/average socio-economic status, geriatric population and alcohol abusers. If not corrected by supplementation, these population groups certainly are more vulnerable to develop atherosclerosis (AS) and subsequently, cardiovascular disease (CVD). Hyperhomocysteinemia per se and/or HHC-induced oxidative stress result(s) in chronic chemical endothelial injury/dysfunction, smooth muscle proliferation, prothrombotic state and oxidation of low density lipoproteins (LDL) leading to diverse cardiovascular complications. In the first decade of the new millennium, major research efforts would be directed towards understanding the basic mechanism of HHC-induced oxidative stress and the pathophysiology of HHC-induced CVD, culminating in the evolution of hitherto unknown therapeutic strategies such as nutriceuticals and oxidant-antidotes.